Professional Team Foundation Server 2012 - Blankenship, Ed (Wrox, 2013)
A comprehensive guide to using Microsoft Team Foundation Server 2012 Team Foundation Server has become the leading Microsoft productivity tool for software management, and this book covers what developers need to know to use it effectively. Fully revised for the new features of TFS 2012, it provides developers and software project managers with step-by-step instructions and even assists those who are studying for the TFS 2012 certification exam. You'll find a broad overview of TFS, thorough coverage of core functions, a look at extensibility options, and more, written by Microsoft insiders and MVPs. An update of the leading Wrox book on Team Foundation Server, written by an expert team of Microsoft insiders and MVPs Provides a broad overview of Team Foundation Server for developers, software project managers, testers, business analysts, and others wanting to learn how to use TFS Offers administrators the necessary tools to efficiently monitor and manage the TFS environment Covers core TFS functions including project management, work item tracking, version control, test case management, build automation, reporting, and how to write extensions for TFS 2012 Professional Team Foundation Server 2012 builds on the proven Wrox Professional formula to give you a solid background in this software management tool.
Includes bibliographical references and index. - Online resource; title from cover page (viewed September 5, 2013)
Keywords: Computer software -- Development -- Computer programs; Computer software -- Management; Teams in the workplace -- Data processing; Logiciels; Gestion; Équipes de travail; Informatique; Computer software; Development; Computer programs; Computer software; Management; Teams in the workplace; Data processing